A didatização dos gêneros textuais reportagem e comentário com foco na distinção entre fato e opinião - Benicio, Gisele Barroso (2023)
The main goal of this paper is to didacticize the categories of fact and opinion through journalistic media texts, specifically report and commentary. This didactic proposal materializes in a workbook elaborated as the final product of this research, to be applied in class with 7th graders. We started from the difficulties presented by students in class concerning the descriptor 14 – to distinguish fact from opinion in texts. The difficulties observed arose from the questions asked in class, when discussing and correcting the Diagnostic Network Assessments (Avaliações Diagnósticas da Rede – ADR), applied by the Municipal Department of Education of the city of Fortaleza. We observed that the students had difficulties in conceptualizing the words fact and opinion. Thus, we chose to address these difficulties considering the theories of Sociodiscursive Interactionism (SDI) and Text and Discourse Analysis (TDA) in order to facilitate the process of understanding and distinguishing these categories by students. For this purpose, we selected texts that have the covid-19 pandemic as their central theme, since we understand that this is a subject of current concern, consequently being relevant to the social debate in class. We furthermore understand that such theme contributes to the understanding of the process of dissemination of information by the media, orienting the student to an accurate and responsible reading of the facts. Our workbook features two sections of studies and activities. The first one works with the reportage text genre, taking into consideration the study of the text, its production context, and the elements that compose the text structure. Also in this section, we work with the category of fact and opinion, highlighting the production of the opinions expressed, the social responsibility in the emission of facts, furthermore, providing tools for research and fact-checking. The second part of the workbook focuses on the commentary text genre. The goal is to approach such text genre and its relevance in reproducing and sharing the opinions of experts on covid-19. We address the category of opinion, focusing on the responsibility and relevance of the social role of an expert when commenting on a subject. We also aimed at the production of commentary texts by the students, highlighting the social role of respect in the emission of ideas and opinions in social media. Our research aims to work on the concepts of fact and opinion, focusing on their identification and differentiation within texts, working on the argumentation process in the construction of facts and opinions expressed. In this respect, the research contributes to the development of the skill of differentiating fact from opinion, as proposed by the Portuguese Language Reference Matrix. By addressing these concepts and working them into texts, we aim to facilitate their recognition and their consequent differentiation by students. In view of the above, the workbook for class application contributes to the teacher's work as a tool for promoting activities focused on the specific categories of fact and opinion. Due to the approach on activities that promote the use of digital tools, this work corroborates the role of digital literacy of students, enabling them to bring to their daily lives what was discussed in class.